Intravitreal Dobesilate Treatment of Dry Age-Related Macular Degeneration: 12-Months Results - Cuevas, P.; Outeiriño, L.A.; Azanza, C.; Angulo, J.; Giménez-Gallego, G. (Journal of Ocular Diseases and Therapeutics, 2014)
Purpose: To evaluate the 12-month efficacy and safety of intravitreal Dobesilate in dry age-related macular degeneration (ARMD). Patients and Methods: Thirty patients with visual impairment due to dry ARMD received a single intravitreal injection of Dobesilate in the study eye. Ophthalmic evaluation included fundoscopy, spectral-domain optical coherence tomography (SD-OCT) and best-corrected visual acuity (BCVA) prior to therapy and 1 week, 1 and 12-months after treatment. Main Outcome Measures: Mean change in BCVA. Retinal anatomy. Incidence of ocular and non-ocular adverse events. Results: There was a statistically significant increase in mean BCVA at 12 months compared with baseline (0.30±0.04 vs. 0.49±0.06 SEM) (p<0.001). BCVA increased in 26 of 30 eyes (86.7%) and only 4 eyes (13.3%) didn’t show any change. Intravitreal Dobesilate injection resulted in a significant improvement of outer retinal anatomy. Visual improvement was not correlated with age. No ocular or systemic events were reported during the follow-up period. Conclusions: This study confirms the safety of Dobesilate intravitreally injected, as well as the improvement in visual acuity and retinal anatomy at 12 months follow-up. Intravitreal Dobesilate may be a promising therapeutic strategy targeting the inflammatory component of dry ARMD.